Imaginary communities : utopia, the nation, and the spatial histories of modernity - Wegner, Phillip E., 1964- (University of California Press, 2002)
Drawing from literary history, social theory, and political critique, this far-reaching study explores the utopian narrative as a medium for understanding the social space of the modern nation-state. Considering the narrative utopia from its earliest manifestation in Thomas More's sixteenth-century work Utopia to some of the most influential utopias of the late nineteenth and twentieth centuries, this book is an astute study of a literary genre as well as a nuanced dialectical meditation on the history of utopian thinking as a quintessential history of modernity. As he unrave.
Keywords: Orwell, George, -- 1903-1950 -- Criticism and interpretation.; More, Thomas, -- Saint, -- 1478-1535. -- Utopia.; Orwell, George, -- 1903-1950; Utopia (More, Thomas, Saint); American fiction -- History and criticism.; Utopias in literature.; Comparative literature -- American and Russian.; Comparative literature -- Russian and American.; Russian fiction -- History and criticism.; Modernism (Literature) -- United States.; Modernism (Literature) -- Great Britain.; Modernism (Literature) -- Russia.; Space and time in literature.; Nationalism in literature.; Communities in literature.; Utopias.; Utopias; Roman américain -- Histoire et critique.; Utopies dans la littérature.; Roman russe -- Histoire et critique.; Modernisme (Littérature) -- États-Unis.; Modernisme (Littérature) -- Grande-Bretagne.; Modernisme (Littérature) -- Russie.; Nationalisme dans la littérature.; Communauté dans la littérature.; Utopies.; utopian literature.; TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; LITERARY CRITICISM -- Semiotics & Theory.; American fiction; Communities in literature; Comparative literature -- American and Russian; Comparative literature -- Russian and American; Modernism (Literature); Nationalism in literature; Russian fiction; Space and time in literature; Utopias in literature; Great Britain; Russia; United States; Bellettrie.; Utopieën.; Modernisme (cultuur); 16th century.; 19th century.; 20th century.; criticism.; critique.; cultural history.; cultural studies.; ernst bloch.; gilles deleuze.; henri lefebvre.; homi bhabha.; jurgen habermas.; karl mannheim.; literary criticism.; literary history.; literary.; louis marin.; martin heidegger.; mikhail bakhtin.; modernity.; nation state.; paul de man.; philosophical.; philosophy.; political.; politics.; slavoj zizek.; social history.; social studies.; social theory.; thomas more.; utopian narrative.; utopian theory.; utopian.; utopianism.; walter benjamin.; Criticism, interpretation, etc.